ResAttn-recon: Residual self-attention based cortical surface reconstruction - An, Mujun; Chen, Jianzhang; Cao, Yankun; Tao, Kemeng; Wang, Jianlei; Wang, Chun; Zhao, Kun; Liu, Zhi (Frontiers in Physics, 2023)
The accurate cerebral cortex surface reconstruction is crucial for the study of neurodegenerative diseases. Existing voxelwise segmentation-based approaches like FreeSurfer and FastSurfer are limited by the partial volume effect, meaning that reconstruction details highly rely on the resolution of the input volume. In the computer version area, the signed distance function has become an efficient method for 3D shape representation, the inherent continuous nature makes it easy to capture the fine details of the target object at an arbitrary resolution. Additionally, as one of the most valuable breakthroughs in deep learning research, attention is a powerful mechanism developed to enhance the performance of the encoder-decoder architecture. To further improve the reconstruction accuracy of the cortical surface, we proposed ResAttn-Recon, a residual self-attention based encoder-decoder framework. In this framework, we also developed a lightweight decoder network with skip connections. Furthermore, a truncated and weighted L1 loss function are proposed to accelerate network convergence, compared to simply applying the L1 loss function. The IOU curve in the training process achieved a steeper slope and a higher peak (0.948 vs. 0.920) with a truncated L1 loss. Thus, the average symmetric surface distance(AD) for the inner and outer surfaces is 0.253±0.051 and the average Hausdorff distance (HD) is 0.629 ± 0.186, which is higher than that of DeepCSR, whose AD equals 0.283 ± 0.059 and HD equals 0.746 ± 0.245. In conclusion, the proposed residual self-attention-based framework can be a promising approach for improving the cortical surface reconstruction performance.